Letter from Detlev W. Bronk to Harrison Shull - Bronk, Detlev W. (Detlev Wulf) (1948)
Concerns the awarding of a fellowship by the National Research Fellowship Board in the Natural Sciences to Shull.
Keywords: Shull, Harrison; National Academy of Sciences (U.S.); Mulliken, Robert Sanderson; Chemists; Nobel Prize winners; National Research Council (U.S.); Bronk, Detlev W. (Detlev Wulf), 1897-1975; Physicists